The Influence of Marketing Communication and Service Quality on the Satisfaction of Tourists of Air Manis Beach in Padang City, West Sumatra - Malik, David; Rahmatulla, Yogi (Adpebi Science Series, 2024)
The problem in this study is how the influence of marketing communication and service quality on the satisfaction of tourists at Air Manis Beach in Padang City, West Sumatra. This study aims to determine the influence of marketing communication and service quality on the satisfaction of tourists at Air Manis Beach in Padang City, West Sumatra. The types of research used are quantitative and associative. The population in this study is all consumers at Air Manis Beach in Padang City, West Sumatra and the sample in this study is 96 respondents. The sampling technique used in this study is the accidental sampling technique. The analysis method used is multiple regression analysis. The results of this study show that based on the results of the t-test on the Marketing communication variable, it has a positive and significant effect on the satisfaction of Tourists of Air Manis Beach, Padang City, West Sumatra. This is evident from the result where the t-value is calculated 5.022 and the value (sig = 0.000 < 0.05). With df = 96-3 = 93 obtained atable of 1.985, from the above results it can be seen that the tcount > table is 5.022 >1.985, this shows that Ha is accepted and Ho is rejected. So marketing communication has an effect on tourist satisfaction. The Service Quality Variable has a positive and significant effect on the satisfaction of Tourists of Air Manis Beach, Padang City, West Sumatra. This is evident from the result where the t-value is calculated 4.872 and the value (si g = 0.000 < 0.05). With df =96-3 = 93 obtained a table of 1.985, from the above results it can be seen that the tcount > table 4.872 >1.985, this shows that Ha is accepted and Ho is rejected. So the quality of service affects tourists. Based on the results of the F test, the value of Fcal was obtained 87.024 > 3.094,meaning that marketing and service quality together have a positive and significant effect on the variable of tourist satisfaction. The value of the determinant coefficient (R-Square) obtained was 0.668 or 66.8%. This figure shows that 66.8% of tourist satisfaction (bound variable) can be explained by marketing communication and service quality. The remaining 33.2% was influenced by other factors that were not explained in this study.